Archives as a Cultural Phenomenon.”4th Congress of Foreign Researchers of Polish History. Kraków, October 19.–22., 2022.: polski - Janiarczyk, Sylwia; Bubak, Oliwia (Archiwa – Kancelarie – Zbiory, 2022)
Sprawozdanie z panelu "Archives as a Cultural Phenomenon". IV Kongres Zagranicznych Badaczy Dziejów Polski. Kraków, 19–22 października 2022 r.